2015
DOI: 10.1111/apt.13344
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: Saccharomyces boulardii in the prevention of antibiotic‐associated diarrhoea

Abstract: Summary Background Antibiotic‐associated diarrhoea is a common complication of antibiotic use, but it can be prevented with administration of probiotics. Aim To update our 2005 meta‐analysis on the effectiveness of Saccharomyces boulardii in preventing antibiotic‐associated diarrhoea in children and adults. Methods The Cochrane Library, MEDLINE, and EMBASE databases were searched up until May 2015, with no language restrictions, for randomised controlled trials; additional references were obtained from reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(121 citation statements)
references
References 42 publications
3
107
0
11
Order By: Relevance
“…A great number of clinical trials and pre-clinical studies demonstrate the efficacy and safety of S. boulardii for various disease indications 24, 25 , such as irritable bowel syndrome, Crohn’s disease, and diarrhea with different causes. Recently, further evidence suggests that S. boulardii can promote the liver function and ameliorate liver fibrosis 26 , hepatic steatosis 27 , and hepatic injury induced by infection 28 .…”
Section: Introductionmentioning
confidence: 99%
“…A great number of clinical trials and pre-clinical studies demonstrate the efficacy and safety of S. boulardii for various disease indications 24, 25 , such as irritable bowel syndrome, Crohn’s disease, and diarrhea with different causes. Recently, further evidence suggests that S. boulardii can promote the liver function and ameliorate liver fibrosis 26 , hepatic steatosis 27 , and hepatic injury induced by infection 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The role of probiotics in CDI remains poorly defined, based on a paucity of high quality evidence. Meta-analyses of numerous small studies have suggested an adjunctive role when taken alongside other antimicrobials in prevention of initial episodes and recurrence (9598). One large RCT was unable to demonstrate a benefit of probiotics in reducing incident CDI, but did observe a trend toward reduction and with only 1% of the study population developing CDI, it was likely underpowered to detect a true difference (99).…”
Section: Probioticsmentioning
confidence: 99%
“…In children, the reduction was from 20.9 to 8.8% (6 RCTs, n = 1,653, RR 0.43, 95% CI 0.30-0.60, NNT 9, 95% CI 7-12), and in adults, from 17.4 to 8.2% (15 RCTs, n = 3,114, RR 0.49, 95% CI 0.38-0.63, NNT 11, 95% CI 9-15) [11]. …”
Section: Yeast Probioticsmentioning
confidence: 99%
“…The same meta-analysis found that S. boulardii administration reduced the risk of C. difficile -associated diarrhea; however, this reduction was statistically significant only in children (2 RCTs, n = 579, RR 0.25, 95% CI 0.08-0.73) and not in adults (9 RCTs, n = 1,441, RR 0.8, 95% CI 0.47-1.34) [11]. …”
Section: Yeast Probioticsmentioning
confidence: 99%